A lesson to learn from developed countries: The case of state branching deregulation in the US - Jorge Guillén (Estudios de Economía, 2009)
The era of US state branching deregulation started in 1970 and ended up with the enactment of the Riegle Neal Act of 1994. One of the purposes of the branching restriction was to avoid bank concentration. The following paper addresses the influence of the state deregulation on commercial banks' efficiency within the US. We calculate an indicator of bank efficiency using Data Envelopment Analysis (DEA). The efficiency indicator is used as the primary step to analyze the effect of state branching law deregulation on bank's efficiency. The analysis is complemented with a failure prediction model using these DEA scores.
Keywords: G21; G28; E58; E61; 330; data envelopment analysis; input oriented models; interstate branch regulation.